The de-Alzheimerization of age-related dementias: implications for drug targets and approaches to effective therapeutics. (February 2019) - Mullane, Kevin; Williams, Michael
Abstract : Alzheimer's disease (AD) was differentiated from senile dementia (SD) in 1910 due to its early onset and pathological severity. In 1976, this distinction was upended when SD was redesignated as AD to focus efforts and funding in dementia-related research. AD then became conflated with amyloid plaques and, to a lesser degree, neurofibrillary tangles complicating efforts in understanding dementia causality and its treatment. The resultant four-decade search for therapies-based almost exclusively on amyloid was an exercise in futility. While dementia is a complex, multifactorial syndrome, AD is viewed as a homogeneous, linear disease. An amyloid-agnostic approach is necessary to discover therapeutics for age-related dementias.